An analytical review for the estimation of montelukast sodium. Issue 5 (2nd March 2022) - Anant, Arjun; Saha, Moumita; Dhiman, Shubham; Singh, Priti; Kurmi, Balak Das; Gupta, Ghanshyam Das; Asati, Vivek
Abstract: Montelukast is a highly potent and selective receptor antagonist of cysteinyl leukotrienes (CysLT1) used in chronic asthma and vasoconstriction reduction and also used in allergies, swelling, hay fever, and shortness of breath. For the measurement of montelukast sodium in biological and pharmaceutical samples, there are different asynchronous and concurrent analytical methods, such as high‐performance thin layer chromatography, UV spectroscopy, capillary electrophoresis, high‐performance liquid chromatography, and liquid chromatography‐mass spectrometry, have been developed. The pathogenesis of asthma, mechanism of action, and various analytical methods for the detection of montelukast sodium and its combination of dosage forms and biological samples have been described in the present review. Ranjan et al. suggested the reverse phase high‐performance liquid chromatography approach for estimating montelukast in rabbit plasma and found the best limit of detection result of 1.0 ng/mL. Ezzeldin et al. developed a liquid chromatography with tandem mass spectrometry system for the simultaneous detection of combinations of montelukast, gliclazide, and nifedipine. The authors conclude that the studies described in the present manuscript will assist researchers in choosing a simple, rapid, and responsive method for the analysis of montelukast sodium and its combinations.